The Third Dialog State Tracking Challenge - Henderson, Matthew; Thomson, Blaise; Williams, Jason (Proceedings IEEE Spoken Language Technology Workshop (SLT), 2014)
In spoken dialog systems, dialog state tracking refers to the task of correctly inferring the user’s goal at a given turn, given all of the dialog history up to that turn. This task is challenging because of speech recognition and language understanding errors, yet good dialog state tracking is crucial to the performance of spoken dialog systems. This paper presents results from the third Dialog State Tracking Challenge, a research community challenge task based on a corpus of annotated logs of human-computer dialogs, with a blind test set evaluation. The main new feature of this challenge is that it studied the ability of trackers to generalize to new entities – i.e. new slots and values not present in the training data. This challenge received 28 entries from 7 research teams. About half the teams substantially exceeded the performance of a competitive rule-based baseline, illustrating not only the merits of statistical methods for dialog state tracking but also the difficulty of the problem.